ANALISIS PENGARUH ASET, JAMINAN DAN SUKU BUNGA PINJAMAN PERBANKAN TERHADAP KEPUTUSAN KREDIT PARA PELAKU UMKM KECAMATAN SEKUPANG BATAM - E Janrosl, Viola Syukrina (Aksara Public, 2017)
Abstract This study aims to analyze the influence of assets, guarantees and lending rates on credit decisions perpetrators of SMEs Sekupang Batam District. Sampling method used is non probability sampling method by purposive sampling. The sample in this study is the perpetrator of MSME Sekupang District amounting to 96 who take credit in Commercial Banks and Rural Banks. The result of the t test shows that the asset and the interest rate affect the credit decision while the guarantee does not affect the credit decision. This is because the perpetrators of SMEs, especially in the District Sekupang Batam on average do not have a grant that has been used as a requirement in Commercial Banks and Bank Perkreditan Rakyat. Such as vehicles in the form of BPKB cars that can be made in Grade Perkreditan Rakyat is for 1998 and Bank 2015 and above. The results of the F test Assets, Guarantee and Interest Rates Banking loans affect the credit decisions of the perpetrators of SMEs Sekupang Batam District.